1998
DOI: 10.1172/jci429
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mesangial cell proliferation by E2F decoy oligodeoxynucleotide in vitro and in vivo.

Abstract: The transcription factor E2F coordinately activates several cell cycle-regulatory genes. We attempted to inhibit the proliferation of mesangial cells in vitro and in vivo by inhibiting E2F activity using a 25-bp decoy oligodeoxynucleotide that contained consensus E2F binding site sequence (E2F-decoy) as a competitive inhibitor. The decoy's effect on human mesangial cell proliferation was evaluated by [ 3 H]thymidine incorporation. The E2F decoy inhibited proliferation in a concentration-dependent manner, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 61 publications
1
43
0
Order By: Relevance
“…[13][14][15][16] To date, molecular therapeutic strategies using decoy ODN in glomerulonephritis have successfully focused on the direct effect of decoy ODN for transcription factor E2F or nuclear factor (NF)-kB. [17][18][19][20] These transcription factors are related with cell cycle progression and inflammatory diseases after glomerular injury. Another transcription factor AP-1 binds to AP-1 consensus sequences present in numerous genes associated with cell-proliferative response and ECM production, such as TGF-b1, collagen, and PAI-1.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] To date, molecular therapeutic strategies using decoy ODN in glomerulonephritis have successfully focused on the direct effect of decoy ODN for transcription factor E2F or nuclear factor (NF)-kB. [17][18][19][20] These transcription factors are related with cell cycle progression and inflammatory diseases after glomerular injury. Another transcription factor AP-1 binds to AP-1 consensus sequences present in numerous genes associated with cell-proliferative response and ECM production, such as TGF-b1, collagen, and PAI-1.…”
Section: Discussionmentioning
confidence: 99%
“…27,30 E2F decoy oligonucleotides have been shown to be capable of suppressing mesangial cell proliferation in vitro and in vivo. 31,32 ECM-induced cell cycle arrest in mesangial cells was shown to be associated with transcriptional repression of E2F-responsive genes such as c-myc, cyclin A and cdc2. 33 In contrast to these reports, we did not detect a corresponding upregulation of the protein products of E2F-responsive genes in the mesangium of glomeruli in human IgAN.…”
Section: Discussionmentioning
confidence: 99%
“…A number of strategies have been reported to successfully block either E2F-1 function or E2F DNA binding activity (Morishita et al, 1995;Ishizaki et al, 1996;Chiang et al, 1997Chiang et al, , 1998Bandara et al, 1997;Maeshima et al, 1998), and each has been shown to inhibit cell growth. Some of these have been tested as potential therapies for tumours or hyperproliferative diseases with promising results.…”
Section: Discussionmentioning
confidence: 99%